Data authenticity and data value in policy-driven digital collections. Issue 4 (10th November 2014) - Bunakov, Vasily; Jones, Catherine; Matthews, Brian; Wilson, Michael
Abstract : Purpose: – The purpose of this paper is to suggest an approach to data value considerations that is related to the generalized notion of authenticity and can be applied to the design of preservation policies. There has been considerable progress in the scalable architectures for policy-driven digital collection preservation as well as in modeling preservation costs. However, modeling the value of both digital artifacts and collections seems a more elusive topic that has yet to find a proper methodology and means of expression. Design/methodology/approach: – A top-down conceptual analysis was developed and the principles of information technology service management and quality management were applied to the domain of digital preservation. Then, in a bottom-up analysis, the various notions of authenticity in digital preservation projects, reference models and conceptual papers were reviewed. Findings: – The top-down and bottom-up analyses have a meeting point, establishing a close relation between the concepts of data authenticity and data value. Originality/value: – The generalized understanding of authenticity can support the design of sensible preservation policies and their application to the formation and long-term maintenance of digital collections.